Factors Affecting Export of Indonesian Cocoa Beans To Malaysia - Putro, Syaifulloh Albachroini Cahyo; Yusalina; Winandi, Ratna (Jurnal Manajemen & Agribisnis, 2023)
Indonesia is an agricultural country with many superior export products, including cocoa beans. Indonesia was once the third-largest cocoa producer in the world. However, there has been a significant decline in the export quantities of cocoa beans in recent years. This research aims to analyze the factors affecting the export quantities of Indonesian cocoa beans to Malaysia using the Error Correction Model (ECM) method. The cocoa bean commodities recorded in this research are whole or broken, raw or roasted with HS code 1801. The estimation results show that the factors that significantly affect the export quantities of Indonesian cocoa beans to Malaysia in the long term include Indonesia cocoa beans production, the export price of palm oil, and the dummy export duty policy. On the other hand, factors that significantly affect the export quantities of Indonesian cocoa beans to Malaysia in the short term include Indonesia cocoa beans production and the dummy export duty policy. Policy recommendations that can be developed include increasing cocoa production and productivity by simultaneously carrying out intensification and extensification programs, reducing exports of cocoa in the form of beans, and rising exports of cocoa in processed form. Keywords: cocoa beans, ECM, export quantities, long-term, short-term